Analisis Kinerja Keuangan Menggunakan Metode Economic Value Added (EVA) Dan Market Value Added (MVA) Pada Industri PT. Semen Indonesia (PERSERO) Tbk. Periode 2019-2021 - Puji Lestari; Karnila Ali; Nina Lelawati (Jurnal Manajemen DIVERSIFIKASI, 2025)
The development of today's business world is increasingly dynamic and always changing, where every company is competing to improve the quality of the performance of each company, one of which is PT Semen Indonesia (Persero) Tbk. The company, in this case PT Semen Indonesia (Persero) Tbk, must be able to generate maximum profits and maximize shareholder wealth. There are many things that must be considered by the company to attract investors, one of which is showing good financial performance. While the measurement tools used to measure value-added-based financial performance are Economic Value Added (EVA) and Market Value Added (MVA). The design in this study uses a quantitative approach with descriptive statistical methods. The subject of this research is PT. Semen Indonesia (Persero) Tbk. Meanwhile, the object of this study is the income statement report for the 2019-2021 period. The data sources used in this study are primary and secondary, where the primary data is obtained from financial reports and secondary data from literature review, company profiles and company conditions and so on Based on Economic Value Added during 2019-2021, PT Semen Indonesia (Persero) Tbk has added economic value to the company. This is evidenced by the EVA method during 2019-2021 which achieved a positive value in accordance with EVA > 0 criteria set by PT Semen Indonesia (Persero) Tbk. Based on Market Value Added (MVA) at PT Semen Indonesia (Persero) Tbk for the 2019-2021 period, it has added market value in the company. This is evidenced by the MVA method during 2019-2021 which achieved a positive value according to the MVA criteria > 0 set by PT Semen Indonesia (Persero) Tbk